Antibody dynamics in children with first or repeat Plasmodium falciparum infections - Rogier, Eric; Nace, Doug; Dimbu, Pedro R.; Wakeman, Brian; Beeson, James G.; Drakeley, Chris; Tetteh, Kevin; Plucinski, Mateusz (Frontiers in Medicine, 2022)
Immunoglobulin (Ig) production during and after infection with Plasmodium parasites is one of the greatest adaptive immune defenses the human host has against this parasite. Infection with P. falciparum has been shown to induce different B cell maturation responses dependent upon age of patient, number of previous exposures, and severity of disease. Described here are dynamics of Ig responses to a panel of 32 P. falciparum antigens by patients followed for 42 days and classified individuals as showing characteristics of an apparent first P. falciparum infection (naïve) or a repeat exposure (non-naïve). Six parameters were modeled to characterize the dynamics of IgM, IgG1, IgG3, IgA for these two exposure groups with differences assessed among Ig isotypes/subclasses and unique antigens. Naïve patients had significantly longer periods of time to reach peak Ig titer (range 4-7d longer) and lower maximum Ig titers when compared with non-naïve patients. Modeled time to seronegativity was significantly higher in non-naïve patients for IgM and IgA, but not for the two IgG subclasses. IgG1 responses to Rh2030, HSP40, and PfAMA1 were at the highest levels for non-naïve participants and may be used to predict previous or nascent exposure by themselves. The analyses presented here demonstrate the differences in the development of the Ig response to P. falciparum if the infection represents a boosting response, or a primary exposure. Consistency in Ig isotype/subclasses estimates and specific data for P. falciparum antigens can better guide interpretation of seroepidemiological data among symptomatic persons.